COMUNICACIÓN INTERNA, CULTURA ORGANIZACIONAL Y PROMOCIÓN DE LA sALUD: LA VISIÓN DE LOS PROMOTORES PERUANOS DE SALUD - Lic. Andrea PEZO-ÁVILA,Mg. Jorge Lucas VARGAS-SARDÓN,Dra. Eliana GALLARDO-ECHENIQUE (Fonseca, Journal of Communication, 2023)
This research analyzes how the management of internal communication in private health centers in Peru is used to pro-mote an organizational culture based on health promotion among its staff (medical and administrative). In order to identify the managing internal communications and health promotion, a model based on Bustamante’s «six Is» is used.